The Interaction between Adult Cardiac Fibroblasts and Embryonic Stem Cell-Derived Cardiomyocytes Leads to Proarrhythmic Changes in In Vitro Cocultures. (5th January 2016) - Trieschmann, Jan; Bettin, Daniel; Haustein, Moritz; Köster, Annette; Molcanyi, Marek; Halbach, Marcel; Hanna, Mira; Fouad, Mariam; Brockmeier, Konrad; Hescheler, Jürgen; Pfannkuche, Kurt; Hannes, Tobias
Abstract : Transplantation of stem cell-derived cardiomyocytes is one of the most promising therapeutic approaches after myocardial infarction, as loss of cardiomyocytes is virtually irreversible by endogenous repair mechanisms. In myocardial scars, transplanted cardiomyocytes will be in immediate contact with cardiac fibroblasts. While it is well documented how the electrophysiology of neonatal cardiomyocytes is modulated by cardiac fibroblasts of the same developmental stage, it is unknown how adult cardiac fibroblasts (aCFs) affect the function of embryonic stem cell-derived cardiomyocytes (ESC-CMs). To investigate the effects of aCFs on ESC-CM electrophysiology, we performed extra- and intracellular recordings of murine aCF-ESC-CM cocultures. We observed that spontaneous beating behaviour was highly irregular in aCF-ESC-CM cocultures compared to cocultures with mesenchymal stem cells (coefficient of variation of the interspike interval:40.5 ± 15.2 % versus9.3 ± 2.0 %, p = 0.008 ) and that action potential amplitude and maximal upstroke velocity (V m a x ) were reduced (amplitude:52.3 ± 1.7 mV versus65.1 ± 1.5 mV, V m a x :7.0 ± 1.0 V/s versus36.5 ± 5.3 V/s), while action potential duration (APD) was prolonged (APD50:25.6 ± 1.0 ms versus16.8 ± 1.9 ms, p < 0.001 ; APD90:52.2 ± 1.5 ms versus43.3 ± 3.3 ms, p < 0.01 ) compared to controls. Similar changes could be induced by aCF-conditioned medium. We conclude that the presence of aCFs changes automaticity and induces potentially proarrhythmic changes of ESC-CM electrophysiology.